THE ROLE OF RELIGIOUS VALUES IN BUILDING THE CHARACTER OF THE KINGDOM OF SINTANG YOUNGER GENERATION - Dasim, Suparno (Jurnal Civicus, 2015)
This research is motivated by the importance of character buildingin youth. Nowadays many young people occur at Sintang behavior that deviates from the norm. The negative behavior reflects their characters well and can make good citizens did not. Respond to this problem, the kingdom of Sintang perform character building of yaoung generation as education efforts in the community. Question to be answered in this research is how religious values in fostering the young generation and implementation character. Design study used a qualitative approach with a phenomenological method. Subjects in the study was the king Sintang, the man in the kingdom or Sintang, religious leader, community leader, and young leaders. The result showed that the philoshopy and background of the religious values that currently applied by the kingdom of Sintang in accient times are stiil preserved up to now, the implementation of religious values as a form of sustainable development of young pople through the activities of religious sites and the dance breathe Islam.